Efecto antihelmíntico in vitro de extractos de plantas sobre larvas infectantes de nematodos gastrointestinales de rumiantes - Moreno, Fabiana Carina (2010)
With the purpose of studying the anthelmintic efficacy of some plant species presents in Queensland State, Australia, we tested in vitro the effect of plant extracts on infective larvae (L3) migration of Haemonchus placei, Cooperia sp., Haemonchus contortus and Trichostrongylus colubriformis. In general, plant extracts reduced the larval migration of Haemonchus placei and Cooperia sp. The most effective plants against Haemonchus placei and Cooperia sp. (P < 0.0001) were Allocasuarina torulosa, Neolitsea dealbata, Acacia holosericea, Acacia salicina, Callitris endlicheri and Casuarina cunninghamiana. Plants extracts were less effective on L3 migration of Haemonchus contortus and Trichostrongylus colubriformis. Callitris endlicheri, Casuarina cunninghamiana, Acacia farnesiana, Acacia holosericea and Acacia nilotica were the plant extracts that shown an important larval migration inhibition against H. contortus and Trichostrongylus colubriformis (P < 0.0001). Callitris endlicheri was the plant that consistently inhibited the larval migration of every nematode species under study. These in vitro results suggest anthelmintic properties associate with some of the plant species we studied.